Peramalan Jumlah Kasus Baru Covid-19 di Kota Malang: Kajian dengan Analisis Time Series Metode Exponential Smoothing - Dinana Izzatul Ulya; Mahmudah; Hari Basuki Notobroto (Universitas Airlangga, 2024)
Background: COVID-19 is a disease caused by the coronavirus and causes the main symptoms in the form of respiratory problems. The first case of COVID-19 in Indonesia occurred in March 2020. Forecasting COVID-19 cases is important to determine the right strategy for dealing with wider transmission of COVID-19. Time series analysis is a statistical analysis that can make very accurate forecasts, by considering previous data patterns. The Exponential Smoothing Method is one of the methods developed in time series analysis. Objectives: This research aims to forecast COVID-19 cases in Malang City. Methods: This research was conducted at the Malang City Health Service by taking secondary data, namely monthly data on the number of COVID-19 cases from March 2020 to August 2022. Results: Based on the research results, it shows that the number of new cases obtained in September - December 2022 was 856. Single Exponential Smoothing Mode; generated in a mathematical model is Lt = (0,0177)Yt + (0,9823)Lt-1. Conclusions: A study of the number of new COVID-19 cases in Malang City shows fluctuations from 2020-2022. The Single Exponential Smoothing method is the appropriate method for forecasting this research.